2017
DOI: 10.1111/jace.14942
|View full text |Cite
|
Sign up to set email alerts
|

Toward tunable and bright deep‐red persistent luminescence of Cr3+ in garnets

Abstract: Garnet structure (A3B2C3O12) with three different cation sites is a very flexible host material widely used for w‐LEDs, solid‐state lasers, scintillators, and so on. In this work, we have successfully developed six different Cr3+‐doped garnets: Y3Ga4.99Cr0.01O12 (YGG:Cr), Gd3Ga4.99Cr0.01O12 (GGG:Cr), Lu3Ga4.99Cr0.01O12 (LuGG:Cr), Y3Sc1.99Cr0.01Ga3O12 (YSGG:Cr), Gd3Sc1.99Cr0.01Ga3O12 (GSGG:Cr), and Lu3Sc1.99Cr0.01Ga3O12 (LuSGG:Cr), which exhibit persistent luminescence (PersL) due to Cr3+ emission matching well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(36 citation statements)
references
References 45 publications
(93 reference statements)
0
36
0
Order By: Relevance
“…As usual, TL curves and emission spectra of Ca 3 Ga 4 O 9 :0.05Bi 3+ with different release times under different release conditions were measured to clarify the state and role of the traps in different processes . It was found that the Ca 3 Ga 4 O 9 :0.05Bi 3+ phosphor presented a successive trap distribution (300–600 K) after double excitation (254 and 365 nm).…”
Section: Resultsmentioning
confidence: 94%
“…As usual, TL curves and emission spectra of Ca 3 Ga 4 O 9 :0.05Bi 3+ with different release times under different release conditions were measured to clarify the state and role of the traps in different processes . It was found that the Ca 3 Ga 4 O 9 :0.05Bi 3+ phosphor presented a successive trap distribution (300–600 K) after double excitation (254 and 365 nm).…”
Section: Resultsmentioning
confidence: 94%
“…[ 26 ] And the crystal field strength D q and Racha parameters B can be obtained by calculating the relative energy between the Cr 3+ levels. [ 27,28 ] The calculation formulas are shown below [ 29 ] : Dq =E4T210 BDq = normalΔE4TDq210normalΔE4TDq15normalΔE4TDq 8 ΔE4T= E (4T1) E(4T2) where E ( 4 T 1 ) and E ( 4 T 2 ) represent the energy difference between the 4 T 1 level, 4 T 2 level and the ground state 4 A 2 , respectively. The calculated D q / B value is 2.8, larger than 2.3.…”
Section: Resultsmentioning
confidence: 99%
“…Transition metal (TM) ions have significantly higher absorption cross sections due to a stronger coupling to local vibrational odd-parity modes and are investigated to a much lower extent in the context of LT. In contrast to the 4f-4f transitions of the Ln 3+ ions, the spectroscopic properties of the TM ions such as emission and absorption wavelength are influenced by the locally surrounding ligand field of the ions This allows to optimize the thermometric performance of these luminescent ions and tailor it with respect to the practical requirements [14,[21][22][23][24][25][26][27][28][29][30][31][32]. This is especially well manifested in the case of Cr 3+ ions [22,27,28,[30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%